Evaluating a newly developed pharmacogenetic array: screening in a Spanish population. (November 2010) - Almoguera, Berta; Riveiro-Alvarez, Rosa; Gomez-Dominguez, Belen; Lopez-Rodriguez, Rosario; Dorado, Pedro; Vaquero-Lorenzo, Concepción; Dal-Ré, Rafael; Fernandez-Piqueras, Jose; LLerena, Adrián; Abad-Santos, Francisco; Ayuso, Carmen
Aims: How genes affect the response in a patient to a given medication is still poorly understood; the validation of biomarkers and technologies need to be performed. This study aims to determine the analytical characteristics of PHARMAChip ®, a newly developed pharmacogenetic array, and the Spanish population allelic and genotypic frequencies of the genetic variants included in this chip.Materials & methods: The analytical characteristics of PHARMAChip assessed were sensitivity and specificity (for CYP2D6 and SLC6A4 ), accuracy (for SLC6A4 ) and genotyping rate: frequencies of the 90 pharmacogenetic variants of 36 genes were included in PHARMAChip. These were compared in 449 Spanish subjects with data reported in Caucasians.Results & conclusion: Sensitivity and specificity ranged from 96–100%, accuracy was 94.8% and genotyping success rate was 99.6%. PHARMAChip is an accurate, rapid and updatable tool, which may be especially useful for cytochrome P450 testing. The allelic and genotypic frequencies found in the Spanish subjects reinforce the need for establishing possible intraethnic differences among populations prior to performing this kind of study.